Literatura, erotismo e pornografia em O caderno rosa de Lori Lamby de Hilda Hilst - Silva, Alessandra Maria (2017)
Even today, Erotism and Pornography are often disqualified in the literary sphere. The analysis and study of works such as Hilda Hilst's The Pink Notebook by Lori Lamby comes against all the pertinent and classificatory reasons of these elements with literaryness. Scholars such as Sigmund Freud, Susan Sontag, Dominique Mainguenau, Georges Bataille, among others, prove all the literary veracity that makes up this work. Semiotic science aided the whole analysis, transposing in this work the elucidation of this research, that is, it responds to us that Erotism and Pornography are constituent elements of literature, in which they promote a partnership with the others to authenticate their gender, in a sense Congruent with any other. Also the comparison of this work with others, some similar and others different, was a method of truthful discovery proposing an inevitable result in view of the manifestation of literary characteristics that are not let slip.